Bad credit, no problem? Credit and labor market consequences of bad credit reports - Will Dobbie; Paul Goldsmith-Pinkham; Neale Mahoney; Jae Song (Federal Reserve Bank of New York, 2016)
Credit reports are used in nearly all consumer lending decisions and, increasingly, in hiring decisions in the labor market, but the impact of a bad credit report is largely unknown. We study the effects of credit reports on financial and labor market outcomes using a difference-in-differences research design that compares changes in outcomes over time for Chapter 13 filers, whose personal bankruptcy flags are removed from credit reports after seven years, to changes for Chapter 7 filers, whose personal bankruptcy flags are removed from credit reports after ten years. Using credit bureau data, we show that the removal of a Chapter 13 bankruptcy flag leads to a large increase in credit scores and an economically significant increase in credit card balances and mortgage borrowing. We study labor market effects using administrative tax records linked to personal bankruptcy records. In sharp contrast to the credit market effects, we estimate a precise zero effect of flag removal on employment and earnings outcomes. We conclude that credit reports are important for credit market outcomes, where they are the primary source of information used to screen applicants, but are of limited consequence for labor market outcomes, where employers rely on a much broader set of screening mechanisms.
Keywords: D14; J0; G0; 330; consumer finance; bankruptcy; employment